Showing that inverse of an isomorphism is an isomorphism

  • #1
Mr Davis 97
1,462
44
Let ##G## and ##H## be groups, and let ##\phi : G \to H## be an isomorphism. I want to show that ##\phi^{-1} : H \to G## is also an isomorphism. First, note that ##\phi^{-1}## is clearly a bijection as ##\phi## is its inverse. Second, let ##a,b \in H##. Since ##\phi## is surjective, there exist ##x,y \in G## s.t ##a = \phi(x)## and ##b = \phi(y)##. Then ##\phi^{-1}(ab) = \phi^{-1}(\phi(x) \phi(y)) = \phi^{-1}(\phi(xy)) = xy = \phi^{-1} (\phi (x)) \phi^{-1} (\phi(y)) = \phi^{-1}(a) \phi^{-1}(b)##.

Here is my question, why did I only have to use the fact that ##\phi## is surjective and a homomorphism in showing that ##\phi^{-1}## is a homomorphism? Why didn't I have to use that it is injective?
 

Answers and Replies

  • #2
fresh_42
Mentor
Insights Author
2021 Award
17,607
18,184
Let ##G## and ##H## be groups, and let ##\phi : G \to H## be an isomorphism. I want to show that ##\phi^{-1} : H \to G## is also an isomorphism. First, note that ##\phi^{-1}## is clearly a bijection as ##\phi## is its inverse. Second, let ##a,b \in H##. Since ##\phi## is surjective, there exist ##x,y \in G## s.t ##a = \phi(x)## and ##b = \phi(y)##. Then ##\phi^{-1}(ab) = \phi^{-1}(\phi(x) \phi(y)) = \phi^{-1}(\phi(xy)) \stackrel{(*)}{=} xy \stackrel{(*)}{=} \phi^{-1} (\phi (x)) \phi^{-1} (\phi(y)) = \phi^{-1}(a) \phi^{-1}(b)##.

Here is my question, why did I only have to use the fact that ##\phi## is surjective and a homomorphism in showing that ##\phi^{-1}## is a homomorphism? Why didn't I have to use that it is injective?
You did use it. Let's assume ##\phi ## is only surjective and we have ##\phi(u)=\phi(v)##. Then how could we justify ##u=\phi^{-1}(\phi(u))=\phi^{-1}(\phi(v))=v## which you used at the equations I marked with ##(*)\,?## So we actually used ##\phi(u)=\phi(v) \Longrightarrow u=v## which is precisely injectivity.
 
  • Like
Likes Mr Davis 97
  • #3
fresh_42
Mentor
Insights Author
2021 Award
17,607
18,184
One can define injectivity and surjectivity only by means of morphisms. Let's take the example above: ##\phi\, : \,G \longrightarrow H##.

Then ##\phi ## is injective, if and only if for any functions ##\varphi , \psi \, : \, K \longrightarrow G## from a set ##K## with ##\phi \varphi = \phi \psi## follows ##\varphi = \psi \,.##

And ##\phi ## is surjective, if and only if for any functions ##\varphi , \psi \, : \, H \longrightarrow L## to a set ##L## with ##\varphi \phi = \psi \phi## follows ##\varphi = \psi \,.##

If you like you can show the equivalence of these definitions to the usual ones as an exercise. So injectivity is left cancellation and surjectivity right cancellation. For an isomorphisms we need, resp. have both. That's why I said in an earlier thread, that both directions are needed: ##\phi \phi^{-1} = \operatorname{id}_H## and ##\phi^{-1} \phi = \operatorname{id}_G##.
 
  • Like
Likes Mr Davis 97
  • #4
You can't talk about inverse functions if the function is not injective...
 

Suggested for: Showing that inverse of an isomorphism is an isomorphism

  • Last Post
Replies
2
Views
848
  • Last Post
Replies
2
Views
507
  • Last Post
Replies
1
Views
460
Replies
2
Views
520
Replies
3
Views
1K
  • Last Post
Replies
5
Views
241
  • Last Post
Replies
1
Views
3K
  • Last Post
Replies
1
Views
717
  • Last Post
Replies
4
Views
813
Replies
1
Views
1K
Top